1998
DOI: 10.1177/0032885598078002003
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS Education Needs Assessment: A Comparative Study of Jail and Prison Inmates in Northwest Florida

Abstract: To ascertain HIV/AIDS knowledge levels and the education needs of inmates in four jails and two state prisons in northwest Florida, a needs assessment instrument was administered on-site. Because prison inmates receive HIV/AIDS education at intake, it was hypothesized that this group would have greater knowledge levels than jail inmates. On the whole, knowledge levels were good in both groups, with prison inmates scoring somewhat better than jail inmates. Of the 24 items on the questionnaire, only six question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…The rate of AIDS cases among prisoners is six times higher than that of the general population (Hammett, Harmon, & Maruschak, 1999). In light of these statistics, many researchers believe that jail and prison settings, which hold captive and high-risk populations, should be targeted for comprehensive HIV/AIDS educational programming (Hammett et al, 1999;Keeton & Swanson, 1998;National Commission on AIDS, 1991). Prisons and jails provide a stable and highly controlled environment for education (Decker & Rosenfeld, 1995), allowing health educators to reach populations typically difficult to reach in the community (Zimmerman, Martin, & Vlahov, 1991).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of AIDS cases among prisoners is six times higher than that of the general population (Hammett, Harmon, & Maruschak, 1999). In light of these statistics, many researchers believe that jail and prison settings, which hold captive and high-risk populations, should be targeted for comprehensive HIV/AIDS educational programming (Hammett et al, 1999;Keeton & Swanson, 1998;National Commission on AIDS, 1991). Prisons and jails provide a stable and highly controlled environment for education (Decker & Rosenfeld, 1995), allowing health educators to reach populations typically difficult to reach in the community (Zimmerman, Martin, & Vlahov, 1991).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The National Commission on AIDS (1991) reported that inmates return to their communities with inadequate knowledge about behaviors that foster the transmission of HIV. Other studies have shown that inmates have many preconceived misconceptions about the modes of transmission for sexually transmissible infections (STIs; Decker & Rosenfeld, 1995) and underestimate their risk for contracting HIV (Keeton & Swanson, 1998;Zimmerman et al, 1991). Research studies have established that risky behaviors like sexual activity (consensual and nonconsensual), drug use (including needle sharing), and tattooing occur frequently inside many correctional institutions (Krebs, 2002;Krebs & Simmons, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effects of non-traditional prison-based programming on inmate attachments are encouraging. Programs like ACE/CARE benefit facilities by providing comprehensive education/counseling services free to the inmate population and by increasing overall knowledge about HIV and risky behaviors (Collica, 2002; Hammett et al, 1999; Keeton & Swanson, 1998). They assist in increasing self-esteem (Collica-Cox, 2015b; Hammett et al, 1999; Woodall et al, 2015), they reduce disciplinary infractions (Collica-Cox, 2014), they reduce recidivism by promoting viable employment opportunities for females offenders (Collica, 2013; Hammett et al, 1999), and they build supportive communities and networks (Collica, 2010; Collica-Cox, 2015a; Eaton, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…When inmates are not aware of their seropositive infection status, they will not take necessary precautions by limiting high-risk behaviors in order to lower chances of viral transmission both in and outside of prison. Even when inmates are aware of their infection, they remain at an increased risk for transmission because they may not know how to effectively prevent sex and drug-related transmission and contraction (Keeton & Swanson, 1998;Zimmerman, Martin, & Vlahov, 1991) or chose to take few precautions within the prison or in the community. They continue with similar behavioral patterns, thus putting the community at risk.…”
Section: Public Policy Relevancementioning
confidence: 99%